DS DETEKSI SENYAWA PIPERINE DARI CABE JAWA (Piper retrofractum Vahl) UNTUK TERAPI ANTI HIPERKOLESTEROLEMIA STUDI In Silico: DETEKSI SENYAWA PIPERINE DARI CABE JAWA (Piper retrofractum Vahl) UNTUK TERAPI ANTI HIPERKOLESTEROLEMIA STUDI In Silico - Umarudin, Umarudin (Jurnal Komunitas Farmasi Nasional, 2024)
Increased cholesterol levels in the blood characterize Hypercholesterolemia due to excessive fat consumption, leading to an imbalance between fat intake and metabolism. The plant Piper retrofractum Vahl, commonly known as Javanese long pepper, is recognized for its various benefits and properties, including its use in traditional medicine formulations and as a functional food ingredient. The secondary metabolite present in Javanese long pepper is piperine, which imparts a characteristic intense flavor and has been shown to have the potential to lower Hypercholesterolemia, necessitating an in silico study. This research aims to detect the piperine compound from Piper retrofractum Vahl as an anti-hypercholesterolemia therapy through an in silico study. The methodology involves the preparation of compounds using the Pyrx 0.8 application in PDB format, followed by preparing the HMG-CoA Reductase protein using Discovery Studio to remove ligands and water molecules. Molecular docking was conducted using an in silico approach with HEX Cuda 8.0.0 software. The results of the in silico study indicate that piperine from Javanese long pepper interacts with HMG-CoA Reductase, demonstrating a binding affinity value of -317.90 and interacting with three amino acid residues. These findings suggest that Javanese long pepper can be used as an anti-hypercholesterolemia therapy.